PENGARUH PENGHARGAAN, KUALITAS KEHIDUPAN KERJA, KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DOSEN PASCASARJANA POLITEKNIK ANGKATAN LAUT DI SESKOAL JAKARTA - Bambang Nurakhim (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
The purpose of this research was to study the effect of the reward, the quality of work life and job satisfaction on lecturer organizational citizenship behavior Polytechnic Naval Postgraduate School and the Naval Command and Staff Colledge Jakarta. This study uses a quantitative approach with survey method. Samples of this study were 77 lecturers with selected randomly. It can be concluded that: (1) the reward has a direct influence on the organizational citizenship behavior lecturer, (2) the quality of working life has a direct influence on the behavior of organizational citizenship lecturers, (3) job satisfaction has a direct influence on the behavior of organizational citizenship lecturers, (4) reward has a direct influence on job satisfaction lecturer, and (5) the quality of work life has a direct influence on job satisfaction of teachers, and (6) the reward has a direct influence on the quality of work life lecturers. Therefore, to improve organizational citizenship behavior lecturer, reward, quality of work life and job satisfaction should be improved.